Existential insecurity and deference to authority: the pandemic as a natural experiment - Foa, Roberto Stefan; Welzel, Christian (Frontiers in Political Science, 2023)
The global coronavirus pandemic offers a remarkable natural experiment for understanding how sudden exposure to heightened existential risk can affect both individual and societal values. This article examines such an effect via comparative data from eight countries surveyed before and since the worldwide spread of COVID-19 in March of 2020, together with continuous weekly polling tracker data from the United Kingdom from 2019 to 2021. We find that support for political and technocratic authority as well as satisfaction with political institutions rose significantly above long-term historical baselines during the pandemic. Exploring the drivers of this change via multilevel models, reported emotions of fear and stress were found to be positively associated with institutional approval during periods when individuals were exposed to greater pathogen risk. The results support the hypothesis that exposure to existential risk results in greater support for authority, and that individual feelings of insecurity may be linked to less critical citizen orientations.